An Insight into Ayurvedic Aspects of Male Reproductive Health with Special Reference to Preconception Care: A Narrative Review - Sujatha Atheena,; Krishnarajabhatt Hemavathi Shivapura,; Unnikrishnan Parvathy,; Muraleedharan Anjaly, (International Journal of Ayurveda and Pharma Research, 2021)
Reproductive health is a universal concern, a central determinant of quality of life. Male reproductive health disorders can evolve at any phase of life, but accountability of males in maintenance of reproductive and sexual health is seemingly low. Preconception care for men discloses a reproductive health plan, health assessment, health promotion, clinical and psychosocial interventions to improve the adolescent and men in reproductive age groups. In Ayurveda the necessity of sound reproductive health for successful conception is explained under dinacharya (daily regimen), ritucharya (seasonal regimen), sadvritta (code of conduct for keeping good and balanced condition of body and mind), panchakarma (purificatory therapies), rasayana (rejuvenation therapy) and vajikarana (aphrodisiac therapy). Research studies paved less limelight to address the need for preserving the same right from an early phase of life. It is the privilege to avail the possibilities from both ayurvedic and contemporary science to upgrade reproductive health, which in turn enhances positive eugenics. This review is intended with an attempt to detail the ayurvedic aspects of male reproductive health with special reference to preconception care.